1998
DOI: 10.1530/eje.0.1390044
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to thyroid peroxidase in patients with type 1 diabetes in Taiwan

Abstract: Objective: Type 1 diabetes mellitus is frequently associated with autoimmune thyroid disease (ATD). Genetic susceptibility to autoantibody formation in association with ATD and type 1 diabetes mellitus has been described with varying frequencies, but there is still debate about the situation in the Chinese population. We have, therefore, investigated the prevalence of anti-thyroid peroxidase (anti-TPO) in type 1 diabetic patients, and compared the effect of anti-glutamate decarboxylase (anti-GAD) on the thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 34 publications
7
17
1
2
Order By: Relevance
“…In our study, an increased anti-GAD positivity was observed in patients whose duration of diabetes was less than one year compared with that of those whose duration of diabetes was longer than one year; but the difference between two groups was statistically insignificant. Consistent with our results, Chang and his colleagues determined no relations between anti-GAD positivity and duration of diabetes and gender [10].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, an increased anti-GAD positivity was observed in patients whose duration of diabetes was less than one year compared with that of those whose duration of diabetes was longer than one year; but the difference between two groups was statistically insignificant. Consistent with our results, Chang and his colleagues determined no relations between anti-GAD positivity and duration of diabetes and gender [10].…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Chang et al on type 1 diabetics in Taiwan, it was demonstrated that the presence of positive anti-TPO in the presence of anti-GAD was 23.2%. This difference was not statistically significant when compared with the 22% positivity among cases negative for anti-GAD [10]. Premawardhana et al did not find any statistical difference between anti-GAD65/anti-IA-2 positive and negative type 1 DM patients in terms of TA [22].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, in a study of patients with long-standing DM 1 (mean follow-up 18 years) by Umpierrez GE et al, the prevalence of anti-TPO was 33%. In other studies concerning patients with shorter disease duration the anti-TPO prevalence is much lower (19.3% and 21.8% respectively) [19,20]. In a study conducted in Polish population, Madej A. reports the anti-TPO prevalence in 26.9% of patients with mean DM 1 duration of 12.7 years [21].…”
Section: Fig 1 Prevalence Of Anti-tpo According To Tsh After Excludmentioning
confidence: 93%
“…Each disease is thought to be influenced by multiple susceptibility genes, as well as, environmental factors (10). The high prevalence of anti-thyroid peroxidase antibodies (anti-TPO) in patients with T1D prompts the necessity for further thyroid function evaluation (11). Patients with thyroid autoimmunity may also have higher antibody titers to beta cells (12).…”
Section: Introductionmentioning
confidence: 99%